Continuum modeling of {101̄2} twinning in a Mg-3%Al-1%Zn rolled sheet - Jérusalem, A; Fernández, A; Pérez-Prado, M (2010)
A crystal plasticity continuum model with differentiated self- and cross-hardening mechanisms for twin and slip systems has been utilized to predict the slip/twin activities and texture evolution in a rolled and annealed Mg-3%Al-1%Zn sheet compressed along the rolling direction (RD) and tensile tested along the normal direction (ND). The contribution of twinning is significantly larger during tension along ND, leading to a significant texture change with strain. A good correlation is found between simulations and recent experimental results.